Identify the Issuance Problem of Corporate Green Sukuk in Indonesia - Bella Tahya Hania Hania; Endri; Indra (Islamic Economics Journal, 2022)
Sustainable financing is one of the international issues that has been widely discussed due to the issue of climate change. Green sukuk is one of the sustainable financing instruments that are sharia-compliant. However, companies in Indonesia have not shown interest in issuing corporate green sukuk. Various problems and challenges faced by the company to be able to issue corporate green sukuk. The purpose of this study is to know the problem of issuing corporate green sukuk in Indonesia and the best solutions that can be used. The research method used is Analytic Network Process (ANP). In this study, respondents came from experts of corporate green sukuk problems. Total respondents of this research were 5 peoples who came from academia, company actors and regulators. The results show that the main problem in issuing corporate green sukuk is the lack of understanding from market participants. Meanwhile, in terms of solutions, the incentive provided by the government is the main solution to encourage the issuance of corporate green sukuk.